A laboratory-based assessment of mother-child snack food selections and child snack food consumption: Associations with observed and maternal self-report of child feeding practices. (July 2020) - Hepworth, Allison D.; Moding, Kameron J.; Stifter, Cynthia A.
Highlights: Observed child control positively related to higher-energy-density snack choices. Reported teaching about nutrition positively related to higher-ED snack choices. Reported encourage balance and variety negatively related to higher-ED snack choices. Reported encourage balance and variety positively related to lower-ED snack choices. The assessed child feeding practices did not relate to child snack consumption. Abstract: This study explored how mothers' observed and self-reported child feeding practices (child control over food choices, encouragement of balance and variety, and teaching about nutrition) were associated with mother-child snack food selections and child snack food consumption in a laboratory setting. Mothers ( N = 107) and their 4.5-year-old children (52% female) selected up to 5 snack foods (out of 9 snack foods: 6 higher-energy-density [ED] and 3 lower-ED) for optional child consumption throughout a one-hour laboratory visit. Mothers' in-the-moment child feeding practices during the snack food selection task were coded using observational coding schemes, and mothers' global child feeding practices (i.e., across meals and snacking occasions) were self-reported using the Comprehensive Feeding Practices Questionnaire (Musher-Eizenman & Holub, 2007). Results of multiple linear regression analyses with covariates showed that higher-ED snack food selections were positively associated with observed child control over food choices ( B = 0.35, SE = 0.12, p = .006) and self-reported teaching about nutrition ( B = 0.49, SE = 0.19, p = .010), and negatively associated with self-reported encouragement of balance and variety ( B = −0.66, SE = 0.24, p = .007). Lower-ED snack food selections were positively associated with self-reported encouragement of balance and variety ( B = 0.53, SE = 0.20, p = .008). Child consumption of higher-ED or lower-ED snack foods were not significantly associated with mothers' child feeding practices (observed or self-reported). We discuss the implications of these findings for future research on children's snack food selection and consumption.